Nasyid interbatch competition 2024 / Nurul Ain Nadzirah Rendrye and Mahmathi Karuppannan - Rendrye, Nurul Ain Nadzirah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2024)
Under the slogan "The Month of Better Self Reflection, " our yearly Ramadan programme in 2024 has begun, encouraging students to be the greatest versions of themselves. This programme was organised by the Society of Pharmacy Students (SOPHYS) and Faculty of Pharmacy Student Secretariat 2023/2024 during the month of Ramadan, starting on March 12th of this year.